Public managers - Andersen, Jon Aarum (Uprava (Ljubljana), 2012)
This survey article addresses three questions based on the assumption that significant differences exist between public and private organizations. If this assumption is correct managerial and leadership behavior will differ between public and private managers. Additionally, the propensity to change will also differ between public and private managers. Since a number of studies indicate that managers' leadership behavior in public organizations differ from that of private managers, difference and similarities in leadership behavior between women and men in public organizations are examined. Three studies are presented here which show that public and private managers have different behavioral patterns of leadership. However, public managers turn out to be more change-oriented than business managers. In the public organizations investigated no differences in leadership behavior between women and men were found.
Keywords: change-oriented behavior; javna uprava; leadership behavior; managerji; private organization; public organization; spol; vedenje; vodenje